2020
DOI: 10.1002/tal.1781
|View full text |Cite
|
Sign up to set email alerts
|

Optimal design and seismic performance of Multi‐Tuned Mass Damper Inerter (MTMDI) applied to adjacent high‐rise buildings

Abstract: Summary The tuned mass damper inerter (TMDI) is an enhanced variant of the tuned mass damper (TMD) that benefits from the mass‐amplification effect of the inerter. Here, a multi‐TMDI (MTMDI) system (comprising more than one TMDI) linking two adjacent high‐rise buildings is presented as an unconventional seismic protection strategy. The relative acceleration response of the adjacent structures triggers large reaction forces of the inerter devices in the MTMDI, which in turn efficiently improve the seismic perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(28 citation statements)
references
References 64 publications
1
27
0
Order By: Relevance
“…To this end, in recent years, the inertia property of the inerter, defined by Smith 15 as a linear massless mechanical element resisting relative acceleration through the inertance constant, has been leveraged to relax requirements for large secondary mass in suppressing the motion of dynamically excited civil engineering structures via passive dynamic vibration absorbers 16–21 . Among these absorbers, the TMDI, introduced by Marian and Giaralis, 22 was shown to outperform the conventional TMD for the seismic protection of fixed‐based buildings 18,23–28 and base‐isolated buildings, 29,30 as well as for mitigating wind‐borne vibrations in buildings 31–33 and wind turbine towers 34 . In this respect, it was found that the incorporation of an inerter to the TMD can lead to significant attached mass reduction since the inertance scales up practically independently of inerter device physical mass in actual device embodiments 15,35,36 .…”
Section: Introductionmentioning
confidence: 99%
“…To this end, in recent years, the inertia property of the inerter, defined by Smith 15 as a linear massless mechanical element resisting relative acceleration through the inertance constant, has been leveraged to relax requirements for large secondary mass in suppressing the motion of dynamically excited civil engineering structures via passive dynamic vibration absorbers 16–21 . Among these absorbers, the TMDI, introduced by Marian and Giaralis, 22 was shown to outperform the conventional TMD for the seismic protection of fixed‐based buildings 18,23–28 and base‐isolated buildings, 29,30 as well as for mitigating wind‐borne vibrations in buildings 31–33 and wind turbine towers 34 . In this respect, it was found that the incorporation of an inerter to the TMD can lead to significant attached mass reduction since the inertance scales up practically independently of inerter device physical mass in actual device embodiments 15,35,36 .…”
Section: Introductionmentioning
confidence: 99%
“…Numerical results clearly demonstrate that the MTMDI outperforms the multiple tuned mass dampers (MTMD) in control effectiveness and strokes of mass blocks. Domenico and Qiao 34 proposed a multituned mass damper inerter to link two adjacent high-rise buildings. The analysis results show that the optimally designed MTMDI outperforms both conventional MTMD and single tuned mass dampers-inerters (TMDI) in acceleration control.…”
mentioning
confidence: 99%
“…Shock and Vibration e total wind-induced responses of structures can be decomposed into mean value and fluctuating components. Previous literature [8,43,44,49,50] showed that the passive control devices can only suppress the fluctuating vibration, thus while investigating dynamic response characteristics, only the fluctuating response is analyzed. For the clarity of the figures, Figure 6 shows only the 50-second segment of fluctuating displacement time history of the adjacent highrise buildings and the shaded part indicates that the direction of displacement of the two buildings is opposite; i.e., if the sign of one response is negative, the other sign is positive.…”
Section: Comparison Of Displacementmentioning
confidence: 99%
“…e same structure previously considered by De Domenico et al [43] is analyzed as a case, comprising two adjacent high-rise buildings whose main properties are summarized as follows. Building 1 has 59 storeys with 268 meters height and Building 2 consists of 55 storeys with a height of 210.2 meters.…”
Section: A Brief Introduction Of the Two Adjacent High-risementioning
confidence: 99%